2010
DOI: 10.1016/j.econmod.2010.05.014
|View full text |Cite
|
Sign up to set email alerts
|

News and correlations of CEEC-3 financial markets

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 29 publications
(24 reference statements)
3
10
0
1
Order By: Relevance
“…This is similar to previous studies (Buttner and Hayo 2010, Tamakoshi and Hamori 2012, Buchholz and Tonzer 2013. …”
Section: Datasupporting
confidence: 81%
“…This is similar to previous studies (Buttner and Hayo 2010, Tamakoshi and Hamori 2012, Buchholz and Tonzer 2013. …”
Section: Datasupporting
confidence: 81%
“…In addition, both positive and negative news from Germany significantly affected dependence, with the former having a larger influence than the latter, which was consistent with the findings of Yang and Hamori [7]. In contrast to Büttner and Hayo [4] as well as Yang and Hamori [7,8], however, we provided the dynamic process of dependence between the CEEC-3 and Germany and showed that the positive and negative news affected dependence dynamically. Figures 7 and 8 also confirmed that financial contagion occurred during the global financial and European debt crises, consistent with the evidence provided by Boubakri and Guillaumin [14].…”
Section: -Year 5-year 10-yearsupporting
confidence: 70%
“…The first type includes observation-based methods such as those based on the generalized autoregressive conditional heteroskedasticity (GARCH) framework [1,2]. The dynamic conditional correlation (DCC-GARCH)-based approach [3][4][5] and copula-GARCH-based approach [6][7][8] are representative examples. The second type is parameter-based methods.…”
Section: Introductionmentioning
confidence: 99%
“…We formally define return as 8 The majority of studies examining the impact of macroeconomic news announcements and central bank monetary policy settings employ various types of (G)ARCH models in order to examine jointly the conditional volatility and market reaction. Examples assessing the issue on emerging European financial markets include Fišer and Horváth (2010), Egert and Kočenda (2007, Büttner and Hayo (2010), Buttner et al (2012), Hanousek et al (2009), andHanousek andKočenda (2011).…”
Section: Abnormal Returnsmentioning
confidence: 99%